2022
DOI: 10.1177/02841851221100318
|View full text |Cite
|
Sign up to set email alerts
|

Development of a deep learning-based auto-segmentation algorithm for hepatocellular carcinoma (HCC) and application to predict microvascular invasion of HCC using CT texture analysis: preliminary results

Abstract: Background Automatic segmentation has recently been developed to yield objective data. Prediction of microvascular invasion (MVI) of hepatocellular carcinoma (HCC) using radiomics has been reported. Purpose To develop a deep learning-based auto-segmentation algorithm (DL-AS) for the detection of HCC and to predict MVI using computed tomography (CT) texture analysis. Material and Methods We retrospectively collected training data from 249 patients with HCC and validation set from 35 patients. Lesions of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Common automatic segmentation algorithms include fully convolutional network, U-Net, Seg-Net, DeepLab, and their variations [ 40 – 44 ]. Previous studies have shown that such algorithms could generate a satisfactory performance with a Dice coefficient larger than 0.9 for organ segmentation [ 45 , 46 ], while their performance should be further improved for segmenting tumor regions, especially for DSNs [ 47 , 48 ]. In contrast, deep learning analysis of medical images only needs a coarse segmentation of tumor region, such as a bounding box including the whole tumor region, which is easy to achieve and feasible to use in clinical practice.…”
Section: Ai Methodology For Medical Image Analysismentioning
confidence: 99%
“…Common automatic segmentation algorithms include fully convolutional network, U-Net, Seg-Net, DeepLab, and their variations [ 40 – 44 ]. Previous studies have shown that such algorithms could generate a satisfactory performance with a Dice coefficient larger than 0.9 for organ segmentation [ 45 , 46 ], while their performance should be further improved for segmenting tumor regions, especially for DSNs [ 47 , 48 ]. In contrast, deep learning analysis of medical images only needs a coarse segmentation of tumor region, such as a bounding box including the whole tumor region, which is easy to achieve and feasible to use in clinical practice.…”
Section: Ai Methodology For Medical Image Analysismentioning
confidence: 99%